Preliminary studies for a modeling approach regarding floods on the Bia River in Aboisso City - Maïga, Abdoulaye; Sylla, Daouda; Hauhouot, Célestin (The International Hydrographic Review, 2025)
Worldwide, flooding caused by the overflow of rivers is a real threat to people and their property. This is why it is so important to have high-quality data and indicators for modelling this phenomenon. The aim of this study is to determine the morphometric characteristics involved in the flooding process in the Bia watershed upstream Aboisso outlet, and to estimate flood flows statistics both in order to get some insight in the overall features of the river watershed and flood behaviour. To do this, the methodological approach adopted initially enables the morphometric parameters of Bia watershed upstream Aboisso to be determined using empirical formulae and a DTM. Secondly, a frequency analysis is carried out, based on sampling the maximum annual flows generated from the series of average daily flows (1950–1983) from Aboisso station. Various probability laws for extreme values (Gumbel, Weibull and VEG) were fitted to the sample. The results show that the Bia watershed upstream Aboisso outlet covers an area of 8,887 km2, is elongated in shape (KG: 3.58), a low relief (DS: 16.05) and a moderate average slope (IW) estimated at 14.67 %. In addition, the stream which is draining the basin is more than 300 km long, with an average longitudinal slope (I) of 9.6 %. Estimated flood quantiles for return periods T5, T10, T20, T50 and T100 are 368 m3/s, 446 m3/s, 520 m3/s, 616 m3/s and 688 m3/s respectively.